Chemical polymorphism of the essential oils from populations of Thymus caespititius grown on the island S. Jorge (Azores) - Pereira, S. I. (2000)
The compositions of the essential oils obtained from ten populations of Thymus caespititius grown on S. Jorge (Azores) were studied by GC and GC-MS. All the oils analysed were dominated by their monoterpene fraction (69-91%). The sesquiterpene fraction was rather small (4-17%) and consisted mainly of oxygen-containing compounds (3-13%). Enantiomeric ratio of sabinene and [alpha]-terpineol was investigated in the oils from some populations. (+)-Sabinene was detected with high enatiomeric purity (96-99%). Although (+)-[alpha] terpineol was the predominant enantiomer, its purity varied considerably (66-97%). Cluster analysis of all identified components grouped the oils into four main clusters that corresponded with their major components: [alpha]-terpineol (43-68%), carvacrol (32-52%), thymol (44-58%) and sabinene (41%). The essential oil from Th. caespititius showed a clear chemical polymorphism, that was particularly evident among four populations growing along a 200 m distance at Pico Verde.